The development and validation of instrument of teachers’ workload - Si Harun, Mahazi; Omar, Zoharah; Idris, Khairuddin; Basri, Ramli (Contemporary Research Centre, 2015)
The purpose of this study is to test the instrument containing the main factors associated with the list of the teachers’ tasks in order to measure and determine their workload. The respondents consisted of 185 teachers in the secondary schools in Selangor, Malacca and Sabah. The measuring tool used and produced was presented by Abdull, Rahim and Mohamad (2006) and the Ministry of Education (2007). The exploratory factor analysis carried out produced three major components of teachers' workload. These components include curriculum, students' affairs and co-curricular. The result shows that the coefficient of reliability for the workload questionnaire used is 0.933.